Polymer solid electrolyte, preparation method thereof, diaphragm-free lithium secondary battery and lithium secondary battery

By adding polymer additives of fluorine-containing methacrylates and carboxylic acid-containing linear olefin copolymers to the polymer solid electrolyte, the problems of low ion conductivity and poor interfacial compatibility at room temperature of the polymer solid electrolyte are solved, and high ionic conductivity and excellent mechanical properties are achieved.

CN119920968APending Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411263651.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-05-02

Smart Images

  • Figure CN119920968A_ABST
    Figure CN119920968A_ABST
Patent Text Reader

Abstract

The invention provides a polymer solid electrolyte, a preparation method thereof, a diaphragm-free lithium secondary battery and a lithium secondary battery. The solid electrolyte comprises a polymer additive as a component (A), a base polymer as a component (B) and a lithium salt as a component (C), wherein the polymer additive comprises structural units derived from a monomer I and a monomer II; the structural formula of the monomer I is as shown in a formula (I): # imgabs 0 #; the structural formula of the monomer II is as shown in a formula (II): # imgabs 1 #, wherein R1 represents alkyl containing 2-6 carbon atoms and having fluorine atoms; and n represents a positive integer of 3-10. The polymer solid electrolyte provided by the invention has high ionic conductivity, high lithium ion mobility, excellent mechanical strength and stable interfacial compatibility. In addition, the preparation method provided by the invention is simple to operate, high in safety and suitable for mass production, and has practical application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer solid electrolyte, a preparation method thereof, and a diaphragm-free lithium secondary battery and a lithium secondary battery using the polymer solid electrolyte, belonging to the technical field of lithium ion batteries. Background Art

[0002] Traditional lithium batteries use organic solvents as electrolytes, which pose safety hazards such as liquid leakage, fire and explosion; liquid electrolytes cannot withstand high operating voltages, and lithium is an active metal. The two react easily to produce an electrolyte membrane that reacts with other substances, leading to the growth of harmful lithium dendrites. These unfavorable factors make it difficult for lithium-ion batteries to meet the requirements of high energy density and high safety performance. Compared with liquid electrolytes, solid electrolytes have higher ion transport capacity and can achieve more uniform electrochemical deposition, which is the key to achieving high energy density lithium-ion battery cycle stability and performance improvement; secondly, solid electrolytes have the advantages of no leakage, good thermal stability, non-volatility, low risk of spontaneous combustion or explosion, and a wide electrochemical stability window. Therefore, solid electrolytes have become a research hotspot in recent years.

[0003] Polymer solid electrolytes have high safety, good processability and mechanical compliance. In particular, the good adhesion of polymer solid electrolytes can compensate for the volume change of the electrode during charging and discharging, which is beneficial to the stability of the interface and the reduction of interfacial charge transfer resistance. However, polymer solid electrolytes have high crystallinity at room temperature, resulting in insufficient ionic conductivity. In addition, there are problems such as poor compatibility between polymer solid electrolytes and positive and negative electrodes and high interfacial impedance, which hinder their practical application.

[0004] The existing technology has conducted relevant research on improving the ionic conductivity of solid polymer electrolytes:

[0005] Some literature discloses a method for preparing a polyionic liquid electrolyte by photoinitiated polymerization. The polyionic liquid electrolyte has good electrochemical properties and its room temperature conductivity is 2.91×10 -4 S / cm, but the interfacial compatibility problem still exists.

[0006] Some literature discloses a method for preparing a polymer solid electrolyte, in which a nitrile plasticizer is added to a solid electrolyte prepared from a rubber grafted modified substance, and the room temperature ionic conductivity thereof reaches 10 -4 ~10 -3 However, nitrile has certain toxicity, and the polymer solid electrolyte with added nitrile plasticizer has poor interfacial compatibility with lithium metal and large interfacial impedance, so its commercial application range is limited.

[0007] In addition, for lithium-ion batteries, a diaphragm may or may not be used in its structure. The diaphragm material is non-conductive, and its physical and chemical properties have a great influence on the performance of the battery. In the case of using a diaphragm, the main function of the diaphragm is to separate the positive and negative electrodes of the battery to prevent the two electrodes from contacting and short-circuiting. In addition, it also has the function of allowing electrolyte ions to pass through. In the case of not using a diaphragm, the positive and negative electrodes are usually separated by the electrolyte itself to prevent short-circuiting, and the ions are conducted by the electrolyte itself. From the perspective of the energy density of lithium secondary batteries, secondary batteries without diaphragms are advantageous. In particular, the use of solid electrolytes (such as quasi-solid or all-solid electrolytes) makes diaphragm-free batteries possible.

[0008] It can be seen that although a series of studies have been conducted in this field on the improvement of polymer solid electrolytes, there is still room for further improvement in the development of polymer solid electrolytes that have high ionic conductivity, high lithium ion mobility, excellent mechanical strength and stable interface compatibility. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] As mentioned above, polymer solid electrolytes have the characteristics of high safety, good processability and mechanical compliance. However, their low ion conductivity at room temperature and poor interface compatibility limit the development of polymer solid electrolytes.

[0011] The existing technology has achieved the improvement of the ion conductivity of polymer solid electrolytes by introducing plasticizers, inorganic fillers, polymer blending, copolymerization and other methods. However, the problem of poor interface compatibility has not been improved and may even lead to a decrease in mechanical properties.

[0012] In order to solve the above problems, the present invention provides a polymer solid electrolyte, to which a polymer additive is added. After the polymer additive is added, the impedance and interface compatibility problems of the passivation film formed at the contact surface between the solid electrolyte and the electrode can be improved, and the fluorine atoms in the polymer additive promote the ionization of lithium salts, provide more free lithium ions, improve lithium ion mobility and ion conductivity, while maintaining good mechanical properties.

[0013] Furthermore, the present invention also provides a method for preparing a polymer solid electrolyte, which has simple operation, low raw material cost, high safety, is suitable for mass production, and has practical application value.

[0014] Furthermore, the present invention also provides a lithium secondary battery, which comprises the polymer solid electrolyte described above or the polymer solid electrolyte prepared by the preparation method described above.

[0015] Solutions for solving problems

[0016] After in-depth research, it has been found that the above technical problems can be solved by implementing the following technical solutions:

[0017] The present invention first provides a polymer solid electrolyte, wherein the solid electrolyte comprises a polymer additive as component (A), a base polymer as component (B) and a lithium salt as component (C);

[0018] Wherein, the polymer additive comprises structural units derived from monomer I and monomer II;

[0019] The structural formula of the monomer I is shown in formula (I):

[0020]

[0021] The structural formula of the monomer II is shown in formula (II):

[0022]

[0023] Wherein, R1 represents an alkyl group having 2 to 6 carbon atoms and having a fluorine atom;

[0024] n represents a positive integer from 3 to 10.

[0025] According to the above polymer solid electrolyte, the number of fluorine substitutions in the alkyl group in R1 is 4-13.

[0026] According to the above polymer solid electrolyte, wherein n is a positive integer of 4-9.

[0027] According to the polymer solid electrolyte described above, wherein the component (A) is obtained by polymerizing monomers including monomer I and monomer II; the amount of the component (A) is 10% to 55% by mass of the component (B).

[0028] According to the above-mentioned polymer solid electrolyte, the molar ratio of monomer I to monomer II is 1:0.6 to 1:2.5.

[0029] According to the above polymer solid electrolyte, wherein the molecular weight of the component (A) is 4000-10000.

[0030] According to the above polymer solid electrolyte, wherein the base polymer of component (B) comprises a fluorine-containing polymer.

[0031] According to the polymer solid electrolyte described above, the fluorine-containing polymer comprises a combination of one or more of divinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

[0032] In addition, the present invention also provides a method for preparing the polymer solid electrolyte according to the above, which comprises the following steps:

[0033] Mixing a monomer mixture including the monomer I and the monomer II and an initiator in an organic solvent for copolymerization to obtain a copolymer;

[0034] Mixing the base polymer, copolymer and lithium salt in an organic solvent to obtain a mixed solution;

[0035] The mixed solution is formed into a film and dried to obtain a polymer solid electrolyte.

[0036] In addition, the present invention also provides a diaphragm-free lithium secondary battery, wherein the diaphragm-free lithium secondary battery includes or uses the polymer solid electrolyte described above or the polymer solid electrolyte obtained according to the preparation method described above.

[0037] Furthermore, the present invention also provides a lithium secondary battery, wherein the lithium secondary battery comprises or uses the polymer solid electrolyte described above or the polymer solid electrolyte obtained according to the preparation method described above.

[0038] According to the lithium secondary battery described above, wherein the negative electrode in the lithium secondary battery is a lithium negative electrode.

[0039] Effects of the Invention

[0040] The above technical solution of the present invention has the following beneficial effects:

[0041] 1) A polymer additive is added to the polymer solid electrolyte provided by the present invention. The methacrylate structure in the polymer additive is stable to lithium metal, the passivation film formed on the contact surface with the electrode has low impedance and good interface compatibility. The fluorine atoms in the copolymer additive promote the ionization of lithium salts, provide more free lithium ions, improve lithium ion mobility, and simultaneously achieve high ionic conductivity and good interface compatibility.

[0042] 2) The long chain structure of the alkyl carboxylic acid in the polymer additive has good flexibility and can be used as a soft chain to improve the mechanical properties of the polymethacrylate structure.

[0043] 3) In some specific embodiments, especially when PVDF polymers are used as the base polymer, the fluorine atoms in the polymer additive can synergistically act with the fluorine atoms in the PVDF polymer to further promote the dissociation of lithium salts, thereby greatly improving the ionic conductivity of the polymer solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 A tensile strength curve of the polymer solid electrolyte membrane material of Example 1 of the present application is shown. DETAILED DESCRIPTION

[0045] The following is a detailed description of the present invention. The following description of the technical features is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0046] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0047] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0048] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0049] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0050] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".

[0051] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0052] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.

[0053] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.

[0054] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0055] The present invention mainly provides a polymer solid electrolyte, which comprises a polymer additive formed by copolymerization of a fluorine-containing methyl acrylate compound and a straight-chain terminal olefin containing a carboxylic acid group. The addition of the polymer additive reduces the interface impedance and improves the ionic conductivity, lithium ion mobility and mechanical properties of the polymer solid electrolyte.

[0056] The present invention is mainly obtained through the following insights:

[0057] In view of the problem of low ion conductivity of traditional polymer solid electrolytes, some research has been conducted on the improvement of polymer solid electrolytes in the prior art. The ion conductivity of polymer solid electrolytes has been improved by introducing plasticizers, inorganic fillers, polymer blending, copolymerization and other methods. However, while improving the ion conductivity of polymer solid electrolytes, it often has a certain impact on their mechanical strength, resulting in the risk of reduced safety of polymer solid electrolytes. In addition, the problem of poor interface compatibility of polymer solid electrolytes has not been improved.

[0058] Through the research of the present invention, it has been found that the copolymer of fluorine-containing methacrylate compounds and carboxylic acid-containing linear terminal olefins can improve the interfacial compatibility and ionic conductivity, the passivation film formed by the methacrylate polymer chain segment and the electrode contact surface has a small impedance, and the fluorine atoms can promote the ionization of lithium salts, provide more free lithium ions, and improve the lithium ion mobility. In addition, the carboxylic acid-containing linear terminal olefin can improve the mechanical properties of the polymethacrylate structure. The purpose of making the polymer solid electrolyte have high ionic conductivity, high lithium ion mobility, excellent mechanical strength and stable interfacial compatibility is achieved.

[0059] <First aspect>

[0060] A first aspect of the present invention provides a polymer solid electrolyte comprising a polymer additive as component (A), a base polymer as component (B), and a lithium salt as component (C).

[0061] In addition, various functional additive components may be used in the polymer solid electrolyte composition without hindering the realization of the technical effects of the present invention.

[0062] Component (A)

[0063] The polymer additive as component (A) described in the present invention comprises structural units derived from monomers I and II in its molecular structure.

[0064] Wherein, the monomer I is a combination of one or more methacrylate monomers represented by the following structural formula (I):

[0065]

[0066] The monomer II is a combination of one or more of the linear terminal olefins (terminal unsaturated linear alkyl acids) containing carboxylic acid groups represented by the following structural formula (II):

[0067]

[0068] Wherein, in structure (I):

[0069] R1 represents an alkyl group having 2 to 6 carbon atoms and having fluorine atoms. For such an alkyl group, ethyl, propyl, isopropyl, butyl, isobutyl, pentyl, hexyl and the like can be cited. Moreover, in some preferred embodiments of the present invention, the above-mentioned alkyl group in structure (I) can be a straight-chain alkyl group. Further, for such an alkyl group, one or more of the hydrogen atoms therein can be replaced by fluorine atoms. More specifically, for the hydrogen atoms in these alkyl groups, 4 to 13 of them can be replaced by fluorine atoms. In some further preferred embodiments, the number of carbon atoms of the fluoroalkyl group is 3 to 5, and the number of fluorine substitutions is 7 to 11. For such a fluoroalkyl group, specific examples include tetrafluoropropyl, hexafluorobutyl, octafluoropentyl and other fluoroalkyl groups, preferably hexafluorobutyl.

[0070] In some preferred embodiments, the monomer I can be selected from a combination of one or more of hexafluorobutyl methacrylate, tetrafluoropropyl methacrylate, and octafluoropentyl methacrylate.

[0071] In the present invention, by introducing a unit derived from the monomer of the above structure (I) into the structure of component (A), not only the impedance of the solid electrolyte membrane on the electrode surface can be reduced, but also sufficient ionization of the lithium salt can be promoted.

[0072] For structure (II):

[0073] n represents a positive integer, and 10≥n≥3. In some specific embodiments, n is a positive integer of 4 to 9. When the value of n is too small, it is insufficient to provide sufficient flexibility in the structure of component (A), and it is difficult to achieve the effect of improving the mechanical properties of the polymethacrylate polymer; when the value of n is too large, the mechanical properties of the copolymer will be too soft, which may have an adverse effect on the film-forming properties and the cost will be higher.

[0074] In some preferred embodiments, the monomer II is selected from one or more combinations of straight-chain terminal olefinic carboxylic acids such as 5-hexenoic acid, 6-heptenoic acid, and undecenoic acid.

[0075] Furthermore, in some specific embodiments, the molar ratio of the structural units derived from monomer I and monomer II in the polymer of component (A) may be 1:0.6 to 1:2.5, for example, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.3, etc. When the content of monomer I is too high, in some cases, the polymerization reaction may be hindered to a certain extent due to its steric hindrance effect; when the content of monomer I is too low, the fluorine content is low, and in some cases, there may be concerns about the insignificant effect of improving ionic conductivity.

[0076] In addition, for the polymer of component (A) of the present invention, in addition to the structural units derived from monomers I and II, the structure thereof may further include structural units derived from other monomers III without affecting the technical effect of the present invention. Such monomers III may be polymerizable monomers different from monomers I and II, such as (meth) acrylic acid ester monomers, unsaturated olefin monomers, etc. Further, the number of structural units derived from monomers III may be less than 5% of the total structural units in component (A), preferably less than 3%, and more preferably less than 1%.

[0077] In some preferred embodiments, the molecular weight of the copolymer may be 4000-10000, such as 5000, 6000, 7000, 8000, 9000, etc.

[0078] Component (B)

[0079] The base polymer as component (B) described in the present invention is provided as a basic material.

[0080] The type of the base polymer may be a high molecular polymer material, which generally has a higher dielectric constant and can make the lithium salt described below ionized better.

[0081] In some specific embodiments of the present invention, such a polymer matrix can be selected from one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE), polyethylene oxide (PEO), polyvinylidene fluoride-trifluoroethylene-chlorotrifluoroethylene copolymer (PVDF-TrFE-CTFE), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), polyurethane (PU), polyurea (PUA), etc., and preferably one or more combinations of those fluorine-containing polymers.

[0082] In the present invention, it has been found that the fluorine atoms in the component (A) can produce a synergistic effect with the fluorine atoms in the base polymer of the component (B), further promoting the dissociation of the lithium salt. Therefore, in some preferred embodiments, the base polymer contains a PVDF-type polymer, for example, it can contain a polymer selected from difluoroethylene (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene copolymer (PVDF-CTFE) and the like, or a combination of multiple polymers.

[0083] Component (C)

[0084] The lithium salt as component (C) described in the present invention is the source of active ions in the polymer solid electrolyte and is included in the polymer solid electrolyte system. Without the lithium salt, the polymer solid electrolyte will lose the function of conducting active ions and the entire battery will not work.

[0085] Regarding the type of lithium salt, in some specific embodiments of the present invention, the lithium salt can be selected from one or more salts formed by lithium ions and the following anions: PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、N(FSO2)2 - 、C(CF2SO2)3 - 、C2BF2O4 - Preferably, the lithium salt may be lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).

[0086] Polymer solid electrolyte composition

[0087] Regarding the composition of the polymer solid electrolyte of the present invention, from the aspect of improving the electrical properties of the electrolyte, the contents of the various components of the present invention can be arranged as follows:

[0088] Regarding the content of component (A), the content of component (A) is 10% to 55% by mass of the mass of component (B), preferably 15% to 50% by mass, for example, 18%, 20%, 25%, 30%, 35%, 40%, 45% by mass, etc. When the content of component (A) is too low, the effect of improving ion conductivity is limited; when the content of component (A) is too high, there is a concern that the excess carboxylate in the polymer of component (A) may react with the lithium metal negative electrode.

[0089] In principle, there is no particular restriction on the content of component (C), and the general specification of lithium salt dosage in the art can be followed. In some specific embodiments, the content of component (C) is 30% to 65% by mass of the mass of component (B), for example, 35%, 40%, 45%, 50%, 55%, 60%, etc. When the content of component (C) is too low, the measured ionic conductivity may be reduced; when the content of component (C) is too high, it may cause inconvenience in processing and use of the solid electrolyte composition, for example, the solid electrolyte composition is difficult to be processed into a film.

[0090] The (usage) form of polymer solid electrolyte

[0091] Regarding the form of the polymer solid electrolyte of the present invention, in some specific embodiments, the above-mentioned polymer solid electrolyte composition can be provided separately, and such a composition can be prepared into a film material for use. In other specific embodiments, it can be provided in an integrated manner with a separately provided diaphragm.

[0092] <Second Aspect>

[0093] The second aspect of the present invention provides a method for preparing the polymer solid electrolyte described in the above <first aspect>.

[0094] The preparation method of the present invention is not particularly limited in principle, but in some preferred embodiments, from the perspective of processability, it mainly includes the following steps:

[0095] Mixing the monomer mixture including monomer I and monomer II and an initiator in an organic solvent for copolymerization to obtain a copolymer;

[0096] The base polymer, the copolymer obtained by the reaction and the lithium salt are mixed in an organic solvent to obtain a mixed solution;

[0097] The mixed solution is formed into a film and further dried to obtain a polymer solid electrolyte.

[0098] The types and amounts of monomer I and monomer II, base polymer and lithium salt in the monomer mixture are the same as those in the first aspect and will not be described in detail here.

[0099] Regarding the ratio of the added amounts of monomer I to monomer II, in some specific embodiments, the molar ratio can be 1:0.6 to 1:2.5, for example, 1:1, 1:1.2, 1:1.5, 1:1.8, 1:2, 1:2.3, etc.

[0100] The initiator described in the present invention is a free radical initiator, through which monomer I and monomer II (and other polymerizable monomers that may exist) are free radical polymerized to form a copolymer.

[0101] The type of initiator may be selected from, for example, one or more of an azo initiator, an organic peroxide initiator, and the like.

[0102] In some specific embodiments, the initiator that can be used in the present invention may include one or more of azobisisobutyronitrile (AIBN), azobisisoheptanenitrile, dibenzoyl peroxide, diethylhexyl peroxydicarbonate, isopropylbenzene hydroperoxide, tert-butyl hydroperoxide, dodecyl peroxide, tert-butyl perbenzoate, tert-butyl pervalerate, diisopropyl peroxycarbonate, potassium persulfate or ammonium persulfate.

[0103] The amount of the initiator added is 0.25% to 1.5% of the mass of the aromatic allyl ester monomer. When the amount of the initiator added is too little, effective polymerization cannot be achieved; when the amount of the initiator added is too much, the polymerization degree will be too low.

[0104] In principle, there is no particular restriction on the type of organic solvent, as long as the compatibility and processability requirements can be met. For example, it can be selected from at least one of ether, ethanol, acetonitrile, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, tetrahydrofuran, malononitrile, succinonitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, azelaic acid dinitrile and sebacononitrile.

[0105] In addition, the copolymerization reaction can be controlled by, for example, irradiating or heating the polymerization reaction. In some preferred embodiments, heating can be used to cause the polymerization reaction to occur.

[0106] In some specific embodiments, the copolymerization reaction may further include a precipitation step after completion, the precipitation step comprising: mixing the copolymer with a sedimentation solvent, precipitating the copolymer and filtering and drying. The sedimentation solvent may be selected from at least one of methanol, ethanol, petroleum ether, n-hexane, cyclohexane, heptane, carbon tetrachloride, acetone, propanol, water, toluene, and m-xylene. Preferably, in order to make the precipitation more sufficient, the precipitation step may be accompanied by a stirring step. As for the drying temperature and time, the copolymer may be dried in a vacuum drying oven at 50 to 100° C., preferably 60 to 80° C., for 4 to 10 hours, preferably 4 to 8 hours.

[0107] In some specific embodiments, in the mixing step of the base polymer, copolymer and lithium salt, in order to form a homogeneous mixed solution with the copolymer, the polymer base and the lithium salt, a stirring step may be performed, such as magnetic stirring, etc. There is no particular limitation on the stirring time, and in order to fully form a homogeneous mixed solution, the stirring time may be 12 to 36 hours; there is no particular limitation on the stirring temperature, and it may be 30 to 50°C.

[0108] Further, for the method of forming a film of the electrolyte composition, a film forming method such as a solution coating method and an extrusion casting film can be used. In some more specific embodiments, the solution coating method includes applying the solution to a substrate and drying it, removing the substrate, thereby obtaining a film-like polymer solid electrolyte. There is no particular limitation on the substrate, for example, it can be a glass substrate, a ceramic substrate, a stainless steel substrate, a plastic substrate, etc. For the drying temperature and time, it can be dried in a vacuum drying oven at 50 to 100°C, preferably 60 to 80°C for 4 to 10 hours, preferably 4 to 8 hours. After drying, a thin film on the substrate can be obtained. Peeling the film off the substrate (i.e. removing the substrate) can obtain a film-like polymer solid electrolyte. In addition, the obtained film-like polymer solid electrolyte can also be cut into a suitable shape and size as needed, for example, it can be cut into a circular electrolyte membrane of Φ16mm.

[0109] The preparation method of the invention has simple operation, low raw material cost, high safety, is suitable for mass production, and has practical application value.

[0110] <Third Aspect>

[0111] In the third aspect of the present invention, a lithium secondary battery is provided, in particular, a lithium secondary battery comprising or using the polymer solid electrolyte of the above <first aspect> of the present invention or a polymer solid electrolyte prepared according to the preparation method of the above <second aspect>.

[0112] For such a secondary battery, at least a positive electrode, a negative electrode and a solid electrolyte are included. In addition, for the diaphragm, it can be used when necessary. In some specific embodiments, a diaphragm is further used in the lithium secondary battery. There is no particular restriction on such a diaphragm, and an organic porous membrane can be used. In some specific embodiments, as described above, the polymer solid electrolyte of the present invention can be provided or used in an integrally formed manner with the diaphragm provided separately. In some other specific embodiments, the lithium secondary battery is a diaphragm-free lithium secondary battery. Preferably, the lithium secondary battery can be an all-solid-state battery, that is, it is allowed not to contain a liquid electrolyte and a diaphragm inside, and the solid electrolyte is used to isolate the positive and negative electrodes and transmit lithium ions.

[0113] In addition, the positive electrode in the battery can be a lithium oxide doped with a common transition metal. Preferably, the positive electrode can be an NCM or NCA positive electrode. There is no particular limitation on the negative electrode, which can be a negative electrode commonly used in solid polymer batteries. Preferably, the negative electrode is a lithium negative electrode.

[0114] Example

[0115] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0116] Example 1

[0117] A method for preparing a solid polymer electrolyte to which a copolymer of hexafluorobutyl methacrylate and undecylenic acid is added is as follows:

[0118] 1. Preparation of copolymer additive of hexafluorobutyl methacrylate and undecylenic acid:

[0119] Dissolve 6 ml of hexafluorobutyl methacrylate and 8.28 g of undecylenic acid in a conical flask containing 50 ml of DMF, then add 0.092 g (0.75% of the total monomer amount) of thermal initiator AIBN, react in a water bath at 65°C for 6 hours, and stop the reaction. Slowly drop the mixture into a beaker containing 30 ml of methanol, stir for 30 minutes, then filter out the copolymer, and dry it in a vacuum drying oven at 70°C overnight for use.

[0120] 2. Preparation of polymer solid electrolyte membrane

[0121] i. A certain amount of PVDF was dissolved in DMF, and then a copolymer additive equivalent to 50% of the mass of the polymer substrate was added, and a certain amount of LiTFSI (equivalent to 60wt% of the mass of the polymer substrate) was added, and a homogeneous mixture was formed after magnetic stirring at 40°C for 24h.

[0122] ii. The mixture was poured onto a clean glass plate and dried overnight in a vacuum drying oven at 75°C using a solution coating method. The film was then peeled off the glass plate and cut into a Φ16 mm circular polymer solid electrolyte membrane.

[0123] The polymer solid electrolyte membrane prepared above was used for battery assembly and performance testing, as shown in Table 1.

[0124] Example 2

[0125] The difference from Example 1 is that PVDF is replaced by PEO, and the remaining steps are the same as those of Example 1, and a polymer solid electrolyte membrane is made, and the performance test is carried out after assembling into a battery, as shown in Table 1.

[0126] Example 3

[0127] The difference from Example 1 is that the addition amount of the copolymer additive is adjusted from 50 mass % to 15 mass %, and the remaining steps are the same as Example 1. A polymer solid electrolyte membrane is prepared and assembled into a battery for performance testing, as shown in Table 1.

[0128] Example 4

[0129] The difference from Example 1 is that the addition amount of the copolymer additive is adjusted from 50 mass % to 25 mass %, and the remaining steps are the same as Example 1. A polymer solid electrolyte membrane is prepared and assembled into a battery for performance testing, as shown in Table 1.

[0130] Example 5

[0131] The difference from Example 1 is that the addition amount of the copolymer additive is adjusted from 50 mass % to 40 mass %, and the remaining steps are the same as Example 1. A polymer solid electrolyte membrane is prepared and assembled into a battery for performance testing, as shown in Table 1.

[0132] Reference Example 1

[0133] The difference from Example 1 is that the addition amount of the copolymer additive is adjusted from 50 mass % to 5 mass %, and the remaining steps are the same as Example 1. A polymer solid electrolyte membrane is prepared and assembled into a battery for performance testing, as shown in Table 1.

[0134] Reference Example 2

[0135] The difference from Example 1 is that the addition amount of the copolymer additive is adjusted from 50 mass % to 60 mass %, and the remaining steps are the same as Example 1. A polymer solid electrolyte membrane is prepared and assembled into a battery for performance testing, as shown in Table 1.

[0136] Comparative Example 1

[0137] The difference from Example 1 is that the copolymer additive is not added, and the remaining steps are the same as Example 1. A polymer solid electrolyte membrane is prepared, and after being assembled into a battery, performance tests are performed, as shown in Table 1.

[0138] Comparative Example 2

[0139] The difference from Example 1 is that only poly(hexafluorobutyl methacrylate) is used as an additive, and the remaining steps are the same as those of Example 1. A polymer solid electrolyte membrane is prepared, and a performance test is performed after assembling into a battery, as shown in Table 1.

[0140] Performance Testing

[0141] 1. Ionic conductivity: The polymer solid electrolyte membrane (CSEs) prepared above was combined with two stainless steel electrodes (SS) to form a SS / CSEs / SS simulated battery for testing. The battery assembly process was carried out in a glove box with a water and oxygen content of less than 0.1ppm. The electrochemical impedance spectroscopy (EIS) test used a frequency range of 0.01Hz to 106Hz to measure the electrochemical impedance of the polymer solid electrolyte at room temperature. The impedance data obtained from the EIS test was used to calculate the ionic conductivity of the prepared polymer solid electrolyte.

[0142] 2. Cyclic stability: The polymer solid electrolyte sheets (CSEs) prepared above are combined with ternary positive electrodes and lithium metal negative electrodes to form button cells. The preparation of the cells is carried out in a glove box. The cells are tested for charge and discharge cycles at a rate of 0.1C, and the attenuation of their discharge capacity is detected.

[0143] 3. Tensile strength: 20 mm wide polymer solid electrolyte membrane material was cut and tested for tensile strength using a universal tensile machine at a loading rate of 30 mm / min. The results are shown in Table 1. The polymer solid electrolyte membrane material of Example 1 was tested using a universal tensile machine at a loading rate of 30 mm / min to obtain a stress-strain curve, as shown in Table 1. Figure 1 shown.

[0144] Table 1 Performance test results of embodiments, comparative examples and reference examples

[0145]

[0146] It can be seen from Table 1 that in Comparative Example 1, the polymer additive of the present invention is not used, resulting in too low a capacity and failing to meet usage requirements; in Comparative Example 2, only one component is used in the polymer addition, resulting in insufficient tensile strength of the polymer solid electrolyte membrane.

[0147] In addition, Reference Examples 1 and 2 provide some references for the dosage of the polymer additive of the present invention. Although different base polymers may lead to certain changes in the appropriate dosage range of the polymer additive of the present invention, in general, when the content of component (A) of the present invention is 10% to 55% by mass of the mass of the component (B), both cyclability and mechanical stability can be taken into account.

[0148] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present invention should not be limited thereto.

[0149] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A polymer solid electrolyte, characterized in that: The polymer solid electrolyte comprises a polymer additive as component (A), a base polymer as component (B) and a lithium salt as component (C); Wherein, the polymer additive comprises structural units derived from monomer I and monomer II; The structural formula of the monomer I is shown in formula (I): The structural formula of the monomer II is shown in formula (II): Wherein, R1 represents an alkyl group having 2 to 6 carbon atoms and having a fluorine atom; n represents a positive integer from 3 to 10.

2. The polymer solid electrolyte according to claim 1, characterized in that The number of fluorine substitutions in the alkyl group in R1 is 4 to 13.

3. The polymer solid electrolyte according to claim 1 or 2, characterized in that: The n is a positive integer of 4-9.

4. The polymer solid electrolyte according to any one of claims 1 to 3, characterized in that: The component (A) is obtained by polymerizing monomers including monomer I and monomer II; the amount of the component (A) is 10% to 55% by mass of the component (B).

5. The polymer solid electrolyte according to claim 4, characterized in that: The molar ratio of the monomer I to the monomer II is 1:0.6 to 1:2.

5.

6. The polymer solid electrolyte according to any one of claims 1 to 5, characterized in that: The molecular weight of the component (A) is 4,000 to 10,000.

7. The polymer solid electrolyte according to any one of claims 1 to 6, characterized in that: The base polymer of component (B) comprises a fluorine-containing polymer.

8. The polymer solid electrolyte according to claim 7, characterized in that: The fluorine-containing polymer comprises one or more combinations of vinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, and polyvinylidene fluoride-chlorotrifluoroethylene copolymer.

9. A method for preparing a polymer solid electrolyte according to any one of claims 1 to 8, characterized in that: The following steps are involved: Mixing a monomer mixture including the monomer I and the monomer II and an initiator in an organic solvent for copolymerization to obtain a copolymer; Mixing the base polymer, copolymer and lithium salt in an organic solvent to obtain a mixed solution; The mixed solution is formed into a film and dried to obtain a polymer solid electrolyte.

10. A lithium secondary battery without a separator, characterized in that: The separator-free lithium secondary battery comprises a positive electrode, a negative electrode and comprises or uses the polymer solid electrolyte according to any one of claims 1 to 8 or the polymer solid electrolyte obtained by the preparation method according to claim 9.

11. A lithium secondary battery, characterized in that: The lithium secondary battery comprises or uses the polymer solid electrolyte according to any one of claims 1 to 8 or the polymer solid electrolyte obtained by the preparation method according to claim 9.

12. The lithium secondary battery according to claim 10 or 11, characterized in that: The negative electrode in the lithium secondary battery is a lithium negative electrode.